2011
DOI: 10.3324/haematol.2011.052068
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and mutations in chronic myeloproliferative neoplasms

Abstract: T he BCR-ABL1-negative classic myeloproliferative neoplasms, polycythemia vera (PV), essential thrombocytemia (ET) and primary myelofibrosis are clonal stem cell disorders associated with an increased production of mature blood cells belonging preferentially to one cell linage.1 They share substantial phenotypic mimicry, can undergo phenotypic shifts (from PV to ET and vice versa) as well as evolution to myelofibrosis (post-PV/post-ET myelofibrosis), and all eventually progress to leukemia. The hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
9
0
3
Order By: Relevance
“…Recently, mutations in genes involved in regulating the epigenome in myeloid malignancies (e.g. DNMT3A , TET2 , IDH1 , IDH2 , ASXL1 , and EZH2 ) have been described in MPN (Tefferi & Vainchenker, ; Vannucchi & Biamonte, ). This raises the possibility that an agent, such as panobinostat, which not only targets the JAK/STAT pathway but can potentially also target the deregulated epigenome in myeloid stem and progenitor cells, may represent a novel approach for the treatment of patients with MPN (Fiskus et al , ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mutations in genes involved in regulating the epigenome in myeloid malignancies (e.g. DNMT3A , TET2 , IDH1 , IDH2 , ASXL1 , and EZH2 ) have been described in MPN (Tefferi & Vainchenker, ; Vannucchi & Biamonte, ). This raises the possibility that an agent, such as panobinostat, which not only targets the JAK/STAT pathway but can potentially also target the deregulated epigenome in myeloid stem and progenitor cells, may represent a novel approach for the treatment of patients with MPN (Fiskus et al , ,b).…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 (enhancer of zeste homolog 2) is another key regulator of PRC2 . EZH2 is present on chromosome 7 and is overexpressed in solid tumours such as lymphoma.…”
Section: Histone Modifications and Regulation Of Chromatin Structurementioning
confidence: 99%
“…Specifically, the discoveries of somatic mutations in JAK2, MPL and CALR genes have improved patients' stratification and molecular characterization highlighting the role of Jak-STAT signaling in MPN pathogenesis. However, several evidences indicate that these mutations are not sufficient for disease initiation and progression and that the phenotypes of the disease are highly heterogeneous, suggesting that other unknown genetic or epigenetic factors might be involved 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and also that the mutation order could matter: 16 driver mutations can precede or follow additional somatic mutations in other myeloid genes. Interestingly, recently, it has been demonstrated that most of these genes are associated with age-related clonal hematopoiesis in normal elderly subjects, suggesting that pre-malignant clones may be present many years before disease develops and are required, but insufficient, to result in disease.…”
Section: Introductionmentioning
confidence: 99%